Reducing missed opportunities for vaccination in Mozambique: findings from a cross-sectional assessment conducted in 2017. Issue 12 (30th December 2021) - Magadzire, Bvudzai Priscilla; Joao, Gabriel; Bechtel, Ruth; Matsinhe, Graça; Nic Lochlainn, Laura; Ogbuanu, Ikechukwu Udo
Abstract : Objective: Missed opportunities for vaccination (MOV) are a significant contributor to low vaccination coverage. To better understand the magnitude and underlying causes of MOV among children aged 0–23 months in Mozambique, we conducted an assessment and developed a roadmap for strengthening the country's childhood immunisation programme. Setting: Three provinces in North, South and Central Mozambique. Methods: The assessment applied a mixed-method approach. From a sample of 41 health facilities, we conducted exit interviews with caregivers of children aged 0–23 months (n=546), surveys with health workers (n=223), focus group discussions with caregivers (n=6) and health workers (n=5), and in-depth interviews with health facility managers (n=9). We analysed the data to assess the magnitude of MOV and to identify causes of MOV and ways of preventing them. Results: Vaccination records were available for 538 children. Sixty per cent (n=324) were eligible for vaccination on arriving for their health facility visit. Of these, 76% (n=245) were not fully vaccinated, constituting MOV. Our analysis shows that these MOV were most frequently attributable to practices of caregivers and health workers and also to health systems reasons. Inadequate information about vaccination among both caregivers and health workers, poor or poorly understood health facility practices, inadequate integration of curative and preventative services, inadequate tracking systems to identify children due for vaccination and, less often, limited supply of vaccines, syringes and other related supplies at service points resulted in MOV. Conclusions: The results of the assessment informed the development of roadmaps for reducing MOV that may be applicable to other settings. The global immunisation community should continue to invest in efforts to reduce MOV and thereby make health service visits more effective and efficient for vaccination.